Design and Optimization of Lornoxicam Dispersible Tablets Using Quality by Design (QbD) Approach - Nawaf Almotairi; Gamal M. Mahrous; Saleh Al-suwayeh; Mohsin Kazi (MDPI AG, 2022)
The present study aims to design and optimize the lornoxicam dispersible tablet (LXDT) formulation using the Quality by design (QbD) approach. A randomized Box-Behnken experimental design was used to characterize the effect of the critical factors, such as filler (MCC/Mannitol) ratio, mixing time, and disintegrant concentration, and assessed for their impacts on the critical quality attributes (responses), including dispersibility time, friability, dissolution efficiency, and content uniformity, respectively. The drug-excipients interaction of the formulation was investigated using FTIR and DSC, respectively. The accelerated stability study at 40 °C/75% relative humidity was performed. FTIR revealed an absence of any significant chemical interaction in solid state. DSC thermogram suggested that LX endothermic peak was slightly decreased due to the dilution effect. LXDT formulations exhibited acceptable friability (0.2 to 0.9%). The dissolution efficiency of LXDT formulations ranged from 72.21 to 93.63%. The overall study showed that the optimum level of independent factors was found to be 3:1 MCC/Mannitol, 11 min mixing time, and 6.23% disintegrant concentration. Accelerated stability studies showed the compendial acceptable hardness, friability, and disintegration times. The application of QbD approach can help in the detailed understanding of the effect of CMAs and CPPs on the CQAs on LXDT final product.